Efektivitas beberapa bahan alami yang ditambahkan dalam pakan sebagai pemicu pertumbuhan ikan Nila (Oreochromis niloticus) pada sistem mina padi - Karisoh, Yuriani S.; Manoppo, Henky; Mudeng, Joppy D.; Ngangi, Edwin L. A.; Undap, Suzanne L. (Universitas Sam Ratulangi, 2021)
This study aimed to examine the effect of several types of natural substances in increasing the growth of tilapia optimally. The fish were taken from Board of Fisheries and Freshwater Aquaculture Tatelu (BPBAT), North Sulawesi Province. Fish were acclimatized for a week in ponds in the â€œmina padiâ€ system, with a density of 25 fish/net. After acclimatization, the fish were fed pellet with the addition of ginger (Zingiber officinale), garlic (Allium sativum Linn), and yeast (Saccharomyces cerevisiae) for 30 days as much as 10% /fish body weight /day with the frequency of feeding twice a day, namely at 08.00 and 16.00. This study used a completely randomized design (CRD) with four treatments, namely treatment A: ginger flour 7.5 g/kg of feed, treatment B: garlic flour 15 g/kg of feed, treatment C: Yeast 5 g/kg of feed and treatment D: commercial feed (control), each had three replications. The weight of fish was scaled weekly. The results showed that the growth of fish fed with the addition of bakerâ€™s yeast was better than fish fed with the addition of ginger, garlic, and commercial feed, but statistically the growth of fish fed with bakerâ€™s yeast and ginger were not significantly different from each other.